Patient safety and sense of security when telemonitoring chronic conditions at home: the views of patients and healthcare professionals - a qualitative study - Mirjam Ekstedt; Espen S. Nordheim; Amanda Hellström; Susanna Strandberg; Heidi Hagerman (BMC, 2023)
Abstract Background Chronic diseases are increasing worldwide, and the complexity of disease management is putting new demands on safe healthcare. Telemonitoring technology has the potential to improve self-care management with the support of healthcare professionals for people with chronic diseases living at home. Patient safety threats related to telemonitoring and how they may affect patients' and healthcare professionals' sense of security need attention. This study aimed to explore patients' and healthcare professionals' experiences of safety and sense of security when using telemonitoring of chronic conditions at home. Methods Semi-structured interviews were conducted with twenty patients and nine healthcare professionals (nurses and physicians), recruited from four primary healthcare centers and one medical department in a region in southern Sweden using telemonitoring service for chronic conditions in home healthcare. Results The main theme was that experiences of safety and a sense of security were intertwined and relied on patients´ and healthcare professionals´ mutual engagement in telemonitoring and managing symptoms together. Telemonitoring was perceived to increase symptom awareness and promote early detection of deterioration promoting patient safety. A sense of security emerged through having someone keeping track of symptoms and comprised aspects of availability, shared responsibility, technical confidence, and empowering patients in self-management. The meeting with technology changed healthcare professionals' work processes, and patients' daily routines, creating patient safety risks if combined with low health- and digital literacy and a naïve reliance on technology. Empowering patients' self-management ability and improving shared understanding of the patient's health status and symptom management were prerequisites for safe care and the patient´s sense of security. Conclusions Telemonitoring chronic conditions in the homecare context can promote a sense of security when care is co-created in a mutual understanding and responsibility. Attentiveness to the patient's health literacy, symptom management, and health-related safety behavior when using eHealth technology may enlighten and mitigate latent patient safety risks. A systems approach indicates that patient safety risks related to telemonitoring are not only associated with the patient's and healthcare professionals functioning and behavior or the human-technology interaction. Mitigating patient safety risks are likely also dependent on the complex management of home health and social care service.